Autologous Dendritic Cell Immunotherapy Modulates Renal Perfusion and Hemodynamics in Diabetic Kidney - Soekardi, Adi; Chiuman, Linda; Ginting, Chrismis Novalinda (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Diabetic kidney disease (DKD) is driven by chronic inflammation and endothelial dysfunction, which often persist despite standard pharmacological treatments. Autologous dendritic cell (DC) immunotherapy offers a novel approach to restore immune homeostasis and improve renal vascular function. While the use of autologous DC for immune homeostasis has been previously discussed, not many studies have explicitly reported on the modulation of renal perfusion parameters, such as peak systolic velocity (PSV) and resistive index (RI), following DC immunotherapy. Therefore, this study was conducted to evaluate the effect of autologous DC administration on renal hemodynamics, including PSV and RI, as well as inflammatory biomarkers, including tumor necrosis factor (TNF)-α and vascular cell adhesion molecule (VCAM-1) in DKD patients.METHODS: Thirty-one DKD patients were selected via simple random sampling. All subjects underwent autologous DC therapy, which was administered via intravenous infusion at a concentration of approximately 1×107 cells suspended in 100 mL of normal saline. PSV and RI were measured using Renal Doppler Ultrasonography, while TNF-α and VCAM-1 were quantified using the Enzyme-Linked Immunosorbent Assay (ELISA) method. All measurements were conducted before intervention and 60 days after intervention to evaluate the therapeutic efficacy.RESULTS: DC therapy led to significant alterations in renal hemodynamic parameters. The mean PSV decreased from 52.74 to 38.21 cm/s (p=0.016), while RI showed a modest increase from 0.7350 to 0.7550 (p=0.028). Greater hemodynamic effects were observed in patients with well-controlled glycemia, lower serum urea, and microalbuminuria. In contrast, no significant changes were detected in TNF-α and VCAM-1 levels.CONCLUSION: Autologous DC therapy delivers measurable, statistically significant benefits in renal vascular parameters for DKD, particularly in early-stage disease and metabolically stable patients. These findings may support DC therapy as a promising adjunctive strategy to improve renal microcirculation in DKD. KEYWORDS: diabetic kidney disease, dendritic cell therapy, TNF-α, VCAM-1, PSV, RI